USE OF INFORMATION COMMUNICATION TECHNOLOGIES IN FINANCING INNOVATION PROJECTS IN ENTERPRISES - Shomansurova Zilola Abduvakhitovna (Journal of Artificial Intelligence and Digital Economy, 2024)
This article reveals the use of information and communication technologies in the financing of innovative projects in enterprises in the context of the development of the innovative economy. In the modern period of development of the national economy, innovations become a strategic factor of growth, affect the composition of social production, change the economic structure of society, stabilize the social situation in the country, and ensure dynamic and stable development of the economy. Modern innovations cannot be imagined without advanced information and communication technologies (ICT). ICT is becoming the main tool and environment for the development and implementation of scientific, economic and social activities. It has been thoroughly revealed that the use of information and communication technologies in the financing of innovative projects in enterprises today is the main factor in increasing competitiveness, production efficiency, optimizing management processes, and increasing labor and capital productivity